Making Sense of Toleration
XIII, 184 p. 1 illus.
Keywords: This book brings together a collection of interviews and conversations with leading scholars across different disciplines and areas of research including moral and political philosophy, history, sociology, political theory, psychology, and jurisprudence, among others. It provides an authoritative presentation of contemporary accounts of toleration, their conceptual foundations, and a comprehensive presentation of the different concepts most commonly associated with it (e.g. civility, dignity, coercion, harm, conflict, disagreement, secularism, power, domination, trust, non-interference, neutrality, fairness, pluralism, respect, recognition and ultimately diversity itself). The interviews and conversations published in this volume address some of the most pressing controversies on toleration (and related issues) at both the theoretical and practical levels. Alongside customary refinements of arguments and positions usually embedded in academic conversations, these interviews provide unique insights into the ‘behind the scenes’ on one of the central topics in contemporary scholarly research. Mitja Sardoč is a researcher at the Educational Research Institute in Ljubljana, Slovenia, where he is a member of the Educational Research program and a researcher at the Faculty of Social Sciences, University of Ljubljana. His research interests include citizenship education, patriotism, multiculturalism, toleration, radicalization and violent extremism, education policy, talents and distributive justice, and equality of opportunity.